Construction of a sp3/sp2 Carbon Interface in 3D N‐Doped Nanocarbons for the Oxygen Reduction Reaction. Issue 42 (18th September 2019) - Gao, Jian; Wang, Yun; Wu, Haihua; Liu, Xi; Wang, Leilei; Yu, Qiaolin; Li, Aowen; Wang, Hong; Song, Chuqiao; Gao, Zirui; Peng, Mi; Zhang, Mengtao; et al.
Abstract: The development of highly efficient metal‐free carbon electrocatalysts for the oxygen reduction reaction (ORR) is one very promising strategy for the exploitation and commercialization of renewable and clean energy, but this still remains a significant challenge. Herein, we demonstrate a facile approach to prepare three‐dimensional (3D) N‐doped carbon with a sp 3 /sp 2 carbon interface derived from ionic liquids via a simple pyrolysis process. The tunable hybrid sp 3 and sp 2 carbon composition and pore structures stem from the transformation of ionic liquids to polymerized organics and introduction of a Co metal salt. Through tuning both composition and pores, the 3D N‐doped nanocarbon with a high sp 3 /sp 2 carbon ratio on the surface exhibits a superior electrocatalytic performance for the ORR compared to that of the commercial Pt/C in Zn–air batteries. Density functional theory calculations suggest that the improved ORR performance can be ascribed to the existence of N dopants at the sp 3 /sp 2 carbon interface, which can lower the theoretical overpotential of the ORR. Abstract : Fine‐tuning : Three‐dimensional N‐doped and hierarchical carbon foam (CF) with a specific ratio of sp 3 ‐ and sp 2 ‐hybridized carbon atoms can be prepared from an ionic liquid by simple pyrolysis. This porous carbon material exhibited superior electrocatalytic performance for oxygen reduction reaction (ORR) in the Zn–air battery.